The Appropriation of Product Design as Solution to Minimise Risk of Exertional Heat Illness among Marathon Runners - Mohd Najib, Abdullah Sani; Azrul Amri, Amran; Muhammad Jameel, Mohamed Kamil; Hanim, Romainoor; Louis Ringah, Kanyan (Horizon Research Publishing, 2020)
The intensity of environmental heat stress during a marathon race increases the runner’s metabolic heat production. Based on series of participatory studies and interview sessions with 100 respondents among runners, the contributing factors to this homeostatic imbalance risk are the excessive amount of body-water deficit from extensive sweating, and the rapid increase of cardiovascular and thermal strain while running. In addition, environmental factors such as humidity, the increase of air temperature, wind speed and solar radiation contribute to the marathon runner’s low performance during running with the paucity of cooling strategy that results in the increase of core body temperature with symptoms of exertional heat illness. This paper elucidates the integration of the statistical and theoretical studies of exertional heat illness and the human physiological responses complementing with the product design context. The integration demonstrates the synchronisation of design thinking process within the ergonomics ergosystem framework to develop the appropriate prototype design for marathon runners. As outcome, this research has successfully developed a running suit as its design proposal to minimise exertional heat illness risk and promote the runner’s safety, wellbeing and performance in the heat.